Redes transmidiáticas, diálogos e narrativas de esperança: uma cartografia do imaginário de um programa de TV religioso - Jardim, Ana Paula Teixeira Guimarães (2018)
In the context of network cultures and transmissive communication processes, there is an increasing number of online programs and platforms that are designed to create spaces for conversation. Several of these projects are integrated systems that seek to assist their readers, spectators and followers in overcoming existential problems and thus, adopt motivational discourses. The present master 's research has as objective to carry out a cartography of the social imaginary constituted from the dialogues and the narratives of hope that circulate around a program of Catholic religious television. The corpus of analysis is composed of the transmissive discourses made by the production and presentation of the program and the testimonies sent by viewers via social networks. The theoretical foundation is composed by: Jung (relations between the idea of "hope" and the discourses of religions); Paulo Freire, (concept of hope as persistence); and Lucia Leão (network culture, cartography of the imaginary, method and processes of communication in transmedia). The research method involved: (1) bibliographic research; (2) empirical research composed of surveys of social networking platforms such as Facebook, Twitter and Instagram; and (3) organization and analysis of the data according to the mapping method of narrative imagery. As a result, we have listed: (1) a review of the state of the art on the understanding of the idea of hope in digital social network discourses; (2) development of a system for collecting and mapping data from discourses in social networks; and (3) application, exercise and creation of a mapping of the data collected